Sustainable Development Goals and Physical Education. A Proposal for Practice-Based Models - Salvador Baena-Morales (International Journal of Environmental Research and Public Health, 2021)
The Sustainable Development Goals (SDGs) is a global strategy that aims to obtain a more equitable and just world. These objectives are organized into 17 SDGs, detailing 169 targets. Different international institutions have emphasized the relevance of education to developing citizens who contribute to achieving the SDGs for 2030. However, a review focused on physical education (PE) has yet to be performed. Therefore, the objective of this work is two-fold. First, to analyze and select the specific SDGs that can be implemented in the area of physical education. Second, to relate these specific goals to the different models based on physical education practices. This review showed how three institutional documents have previously related sport, physical exercise, and physical education to specific SDGs. Based on the search done, this review article selects those goals that could be integrated into the educational context through physical education. The bibliographic and critical analysis in this research shows that of the 169 specific goals proposed in the SDGs, only 24 could be worked on in physical education. Upon completion of the analysis, a proposal for the relationship between the practice-based models and these 24 goals is presented. The contributions made in this paper will allow teachers to establish links between PE sessions and SDGs while raising awareness to develop students who contribute to a more sustainable world.